CSVP 2021 abstracts - Murray, Alison M; Street, Hallie; Holmes, Robert B. (Vertebrate Anatomy Morphology Palaeontology, 2021)
Abstract volume for 2021 virtual online meeting of the Canadian Society of Vertebrate Palaeontology